A Feature Analysis of To-Infinitive Sentences (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article examines the study of infinitive and its usage in sentences reveal another aspect of verb infinitives. By explaining the importance of infinitives in clauses, correct ways of applying infinitives in sentences, and the grammatical, syntax analysis of to-infinitive clauses with obvious and clear examples, this manual is intended for the explanation of to-infinitive.